Tabarru Contracts in the Form of Self Guarantee and Providing Something - Nanang Naisabur; Haris Maiza Putra (UIN Sunan Gunung Djati Bandung, 2021)
This study is to discuss the tabarru contract in the form of guaranteeing oneself (Kafalah and Wakalah) and giving something (Grants, Gifts, Waqf, Zakat, Infaq, Alms), where basically the tabbaru contract is giving something (giving something) or lending something. (leding something) adak tabarru the purpose is to help each other. When the tabarru contract has been agreed, it cannot be converted into a tijarah contract whose purpose is to gain profit, except by agreement between the two parties to the contract. However, it is different from the tijarah contract that has been agreed upon, this contract may be changed into a tabarru contract if the party whose rights are retained gives up their rights, thereby canceling the obligations that have not carried out their obligations. The function of this tabarru contract, apart from the orientation of this contract, is to seek the afterlife, not for commercial purposes. However, in its development, this contract is often related to commercial transaction activities, because this tabarru' contract can function as an intermediary that bridges and facilitates the tijarah contract